Pengaruh Model Personalized System For Instruction Terhadap Peningkatan Kebugaran Jasmani Siswa Esktrakulikuler Beladiri Karate Sekolah Menengah Atas Pada Masa Pandemic Covid-19 - Hesti Nur Utami; Ega Trisna Rahayu; Saepul Ma’mun (Peneliti.net, 2021)
This study means to determine the effect of the personalized system for instruction models on improving students' physical fitness in karate extracurricular activities at SMA Negeri 1 Purwakarta. The method used in this research is experimental with one group pretest posttest design. The population in this study were students who took karate extracurricular at SMA Negeri 1 Purwakarta, and the sample used in this study was 17 participants who took part in karate extracurricular where the sampling technique adopted was purposive random sampling. The instrument used in this study was a high school physical fitness test. Statistical analysis used to test the hypothesis using the t test with the results t_(count ) < t_table 0.000 < 0.05, then Ho is rejected. So that the results of the study show that there is an effect of the personalized system for instruction model on increasing students' physical fitness in karate extracurricular activities at SMA Negeri 1 Purwakarta.